Neuropeptides Involved in Facial Nerve Regeneration - Inhyeok Kim (MDPI AG, 2021)
Neuropeptides and neurotransmitters act as intermediaries to transmit impulses from one neuron to another via a synapse. These neuropeptides are also related to nerve degeneration and regeneration during nerve damage. Although there are various neuropeptides, three are associated with neural regeneration in facial nerve damage: calcitonin gene-related peptide (CGRP), galanin, and pituitary adenylyl cyclase-activating peptide (PACAP). Alpha CGRP in facial motoneurons is a signaling factor involved in neuroglial and neuromuscular interactions during regeneration. Thus, it may be a marker for facial nerve regeneration. Galanin is a marker of injured axons rather than nerve regeneration. PACAP has various effects on nerve regeneration by regulating the surrounding cells and providing neurotrophic factors. Thus, it may also be used as a marker for facial nerve regeneration. However, the precise roles of these substances in nerve generation are not yet fully understood. Animal studies have demonstrated that they may act as neuromodulators to promote neurotrophic factors involved in nerve regeneration as they appear early, before changes in the injured cells and their environment. Therefore, they may be markers of nerve regeneration.